CHROMATOGRAPHIC ANALYSIS OF Blumea lanceolaria (Roxb.) Druce LEAF EXTRACT: A TRADITIONAL HERBAL DRUG OF NORTH-EAST INDIA (Applied Biological Research, 2023)
The North-Eastern region of India is hotspot of many medicinal herbs.  Blumea lanceolaria from family Asteraceae is a traditional medicinal herb  of North East India. The present study was aimed to screen the phyto chemical constituents and identify bioactive compounds in crude extracts  of B. lanceolaria using gas chromatography-mass spectroscopy. The  extracts were obtained by Soxhlet extraction in three solvents (methanol,  n-hexane, and chloroform). The identification and characterization of  bioactive compounds in the extracts was performed using GC-MS.  Qualitative phytochemical screening was done for the presence of  flavonoids, phenols, phytosterols, tannins and alkaloids. The study showed  that thphytochemicals were higher in methanolic extract than exane-extracts. In GC-MS analysis a total of five compounds were detected in each sample. Chloroacetic acid, tetradecyl ester was found in methanol (18.15%) as well as in n-hexane extracts  (18.83%) in diverse quantities. Likewise,compounds including 3, 7, 11, 15- tetramethyl-2-hexadecen-1-ol and Z,z-6,28-heptatriactontadien-2-one were  and chloroform extracts. 1-Heptacosanol was identified  in both n-hexane and chloroform extracts. The study reveals that crude  extracts of B. lanceolaria is a potential source of naturally occurring  s, so may be used in traditional medicines.
Keywords: Bioactive; Blumea lanceolaria extracts; medicinal herb; phytochemicals; solvents